Creating opportunities for change and organization development in Southern Africa - Sulamoyo, Dalitso Samson (Contemporary trends in organization development., 2012)
This book takes the position that successful OD applications in cross-cultural settings are predicated on the ability of OD experts to localize them for purposes of suiting local conditions and context. Cultural frameworks have been utilized by global OD experts to understand the general cultural settings of environments in which they are working and applying OD techniques. However, the complexities of culture within organizations, communities and countries may not always be understood within these cultural frameworks and models. Assumptions of culture based or reliant on models alone can impede the successful applications of OD. The author discusses the role of cultural translations of OD techniques within a southern African context. It examines the approach of western consultants in a southern African environment as well as the approach of local southern African consultants as they interact with western developed OD applications in their own local environments.The book uses three methods for conveying the opportunities and experience of OD in southern Africa: research, practitioner point of view, and storytelling. The author recognizes the works of renowned African scholars in the field of management as well OD practitioners carrying out innovative and pioneering work in southern Africa. Their work may not have had much exposure in the West; however, their contributions to the field of management should be recognized. OD is discussed in this book as an opportunity for change and development for southern African countries that are in democratic transitions, post conflict environments and on a path of development. The future of OD is explored within the context of economical, global and political emerging issues. The time is right for change and development in southern Africa with OD as the driving force.